“Determinants of Life Expectancy: Comparative Analysis for Different Groups of Countries Using Panel Regression” - Trpkova nestorovska, Marija (Faculty of Economics-Skopje, 2018)
This paper examines the factors that influence the life expectancy at birth in three groups of countries (countries with high life expectancy, countries with medium life expectancy and countries with low life expectancy) using the panel regression model. Four variables are included in the analysis, gross domestic product per capita, fertility rate, immunization and urbanization. Gross domestic product per capita (as indicator for level of income and economic growth) and urbanization (as indicator of social growth) prove to be statistically significant variables in all three groups. Fertility rate is significant in countries with low and medium life expectancy, while immunization is proven to be insignificant variable. The conclusion is the main focus must be on the economic and social growth. Governments should implement measures that will provide employment and growth in salaries, and also they should create budget that supports investment in infrastructure, health, education and clean environment. If these measures are implemented, on a long run they should contribute to increased quality of living and growth in the life expectancy at birth.
Keywords: Life expectancy at birth, panel regression, GDP per capita, fertility rate, urbanization